The effect of coating concentration of curcumin: H2O on copper winding characteristics - Abidin, Zainal; Siswanto, Eko; Wijayanti, Widya; Winarto (Eastern-European Journal of Enterprise Technologies, 2023)
Each coil of copper produces a magnetic field and the total field inside the solenoid will be the sum of the fields caused by each coil of current. If the solenoid coils are very closely spaced, the internal field will be essentially parallel to the axis except at the very ends. To find out the magnitude of the magnetic field inside the solenoid, you can use Ampere’s law, namely B=μo∙N∙I, where B is the magnetic field strength (T), µo is air permeability (4×10‒7 T m/A), N is the number of turns and I is an electric current. The value of B depends on the number of turns per unit length, N, and current I. The field is independent of the position inside the solenoid, so the value of B is uniform. This only applies to infinite solenoids, but is a good approximation for actual points that are not near the ends of the solenoid. The research object is 4 identical copper coils with a length of 3 cm, a coil diameter of 2 cm, a cross section of 1.5 mm2 with an inductance value of 2.17 µH. Before coating curcumin on the copper winding, the initial value of the magnetic field strength was 2.54 µTesla. After the coating process of curcumin:H2O concentration, the value of the magnetic field strength increased. The method used was immersing 4 copper coils with an inductance value of 2.17 µH in curcumin:H2O concentration in a 100 ml volume measuring cup, with the respective concentrations: (20 %:80 %), (40 %:60 %), (60 %:40 %), (80 %:20 %) in a certain time. Then the copper coil conductor is supplied with a 5-volt DC voltage source. Then the value of the magnetic field strength (B) and electric current is measured, the results are compared with the system before immersing the copper coil. The measurement results showed that the values of electric current and magnetic field strength increased after curcumin coating compared to before treatment. To see the bonding performance of curcumin and copper, the FTIR test and simulation of the curcumin: copper bond were carried out using Avogadro software. In the IR test, there is a strong absorption of aromatic C-C from 1,650 cm-1 to 1,500 cm-1. Whereas in the simulation, the bond between copper and curcumin produces a bond energy of 164.532 kJ/mol or equivalent to 171.12×10-2 eV